2020
DOI: 10.1021/acs.biomac.0c01098
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Water Structure, Hydration Forces, and Mechanical Properties of Polysaccharide Films

Abstract: The interaction of polysaccharides with water has a critical impact on their biological function as well as their technological applications. We performed ellipsometry experiments at different relative humidities (RH) to measure the equilibrium swelling of ultrathin films of different polysaccharides: native and modified phytoglycogen (PG) nanoparticles, dextran, and hyaluronic acid. For RH > 70%, the swelling of hydrophilic polymers with increases in RH is described by hydration forces that are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Although the chemical composition of phytoglycogen is simple, consisting only of AGUs, its dendritic architecture results in complex physical properties. , Small-angle neutron scattering (SANS) revealed that the nanoparticles have a uniform radial density, consistent with measurements and simulations of dendrimer molecules consisting of flexible chains. , SANS measurements of native and hydrophobically modified phytoglycogen nanoparticles also revealed that short flexible chains of AGUs decorate the surface of the nanoparticles, which is consistent with an additional relaxation mechanism observed in rheology measurements of concentrated dispersions of the nanoparticles . We performed osmotic pressure measurements over the complete range of phytoglycogen concentrations measured using dialysis, ellipsometry, and gravimetric analysis; and these measurements allowed us to determine the bulk modulus K of the nanoparticles and its dependence on their hydration.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although the chemical composition of phytoglycogen is simple, consisting only of AGUs, its dendritic architecture results in complex physical properties. , Small-angle neutron scattering (SANS) revealed that the nanoparticles have a uniform radial density, consistent with measurements and simulations of dendrimer molecules consisting of flexible chains. , SANS measurements of native and hydrophobically modified phytoglycogen nanoparticles also revealed that short flexible chains of AGUs decorate the surface of the nanoparticles, which is consistent with an additional relaxation mechanism observed in rheology measurements of concentrated dispersions of the nanoparticles . We performed osmotic pressure measurements over the complete range of phytoglycogen concentrations measured using dialysis, ellipsometry, and gravimetric analysis; and these measurements allowed us to determine the bulk modulus K of the nanoparticles and its dependence on their hydration.…”
Section: Introductionsupporting
confidence: 67%
“…15 We related the water structure measured using infrared (IR) spectroscopy for ultrathin films to the hydration forces acting within the nanoparticles, determining that the hydration water within phytoglycogen nanoparticles is highly ordered relative to that in other polysaccharides. 11 We recently extended this analysis to further correlate the water structure and hydration forces with the bulk modulus of the nanoparticles, 16 showing that an increase in the water ordering leads to a linear increase in the bulk modulus and a corresponding inverse change in the spatial extent of hydration forces. The relatively small value of the bulk modulus K and its sensitive dependence on the hydration of the nanoparticles and water ordering revealed by the osmotic pressure and IR spectroscopy measurements suggest a complex interplay between the uptake of water by the nanoparticles and their mechanical modulus.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PG NPs are highly branched polymer NPs consisting of anhydroglucose units (AGUs) and having a dendritic or tree-like polymer architecture, which differs fundamentally from the gel-like nature of microgel and nanogel particles. , Their porous nature results in significant water uptake, with the sorbed water more strongly bound and highly ordered than for linear polysaccharides . There is an intimate link between the stiffness of the particles and the amount of hydration water, with dehydration of the particles producing an increase in the mechanical modulus of several orders of magnitude. The outer surface of the particles is decorated with short chains of AGUs, which results in an additional relaxation mechanism in rheology measurements and affects the interaction between particles in concentrated dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In addition, polysaccharides also possess the significant advantage of a defined monomer structure that allows their rational modification and the precise tuning of their properties. [10][11][12] Numerous delivery systems, including polysaccharide-based systems, have been investigated for transdermal applications and demonstrated notable success in the delivery of small molecules. 1,[13][14][15][16][17] However, transdermal delivery of high molecular-weight molecules, remains challenging.…”
Section: Introductionmentioning
confidence: 99%